The Level of Habits of Mind to Basic Fourth Grade Pupils in Social Studies and its Relationship with Many Variables - Sallom, Taher; Hamadan, Maisaa; Al-kadi , Lama (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed at assist the level of habits of mind (persisting, managing impulsivity, and striving for accuracy) in social studies to basic fourth grade pupils and to identifying the relationship with gender and work of mother. For that, the descriptive method was used, and prepared a reliable validate scale to measure habits of mind in Social studies. The simple random sample consisted of (300) fourth grade pupils in Lattakia province. The results showed that the level of habits of mind to basic fourth grade pupils is good in social studies. In addition, There were no significant differences among Females and male` scores on scale of habits of mind in social studies in general and in each habit individually, and There were no significant differences among habits of mind in social studies due to the work mother in general and in each habit individually too. In addition, urban pupils` scores on managing impulsivity more than rural pupils’ scores. So, The research recommended in the light of the results of study to Necessity of use habits of mind in social studies and other subjects for development of performance, and the use of program based on habits of mind in teaching.